The role of amyloid PET in patient selection for extra-ventricular shunt insertion for the treatment of idiopathic normal pressure hydrocephalus: A pooled analysis. (August 2021) - Mallon, Dermot H.; Malhotra, Paresh; Naik, Mitesh; Edison, Paul; Perry, Richard; Carswell, Christopher; Win, Zarni
Highlights: Patient selection for the treatment of iNPH is challenging. Comorbid Alzheimer's disease has been suggested as a cause of poor response to shunting. Therefore, amyloid PET has been reported as a method of improving patient selection. However, this pooled analysis of 38 patients does not support this practice. Abstract: Background: Idiopathic Normal Pressure Hydrocephalus (iNPH) can be effectively treated through shunt insertion. However, most shunted patients experience little or no clinical benefit, which suggests suboptimal patient selection. While contentious, multiple studies have reported poorer shunt outcomes associated with concomitant Alzheimer's disease. Prompted by this observation, multiple studies have assessed the role of amyloid PET, a specific test for Alzheimer's disease, in patient selection for shunting. Methods: A comprehensive literature search was performed to identify studies that assessed the association between amyloid PET result and the clinical response to shunting in patients with suspected iNPH. Pooled diagnostic statistics were calculated. Results: Across three relevant studies, a total of 38 patients with suspected iNPH underwent amyloid PET imaging and shunt insertion. Twenty-three patients had a positive clinical response to shunting. 18/28 (64.3%) of patients with a negative amyloid PET and 5/10 (50%) with a positive amyloid PET had a positive response to shunting. The pooled sensitivity, specificity and accuracy was 33.3%, 76.2% and 58.3%. None of these statistics reached statistical significance. Conclusion: The results of this pooled analysis do not support the selection of patients with suspected iNPH for shunting on the basis of amyloid PET alone. However, due to small cohort sizes and weakness in study design, further high-quality studies are required to properly determine the role of amyloid PET in assessing this complex patient group.